THE EFFECTIVENESS OF A TRAINING PROGRAM IN THE DEVELOPMENT OF MATHEMATICAL CONCEPTS AND SKILLS AMONG SOCIAL STUDIES TEACHERS - Dr. Essa A. Alibraheim, Prof.Kamel D. Al-hussary (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of the current research is to prepare a training program to provide social studies teachers with the mathematical concepts and skills necessary to not only teach social studies, but to measure the effect of this training program on the development of their teaching performance. To achieve these goals, the content of social studies books, activity notebooks, and teacher guides from Grades 4 to 6 were analyzed in order to identify a list of the necessary mathematical concepts and skills needed. A test was prepared to measure the acquisition of mathematical concepts and an observation card was prepared to track teaching performance. The instruments were applied to 33 of social studies teachers who were randomly selected from the El-Bagour Educational Administration in Menofia Governorate, Egypt. A quasi-experimental research design was used to identify their weaknesses in mathematical concepts and skills and to determine their teaching performance. The results of this study showed that social studies teachers possess the mathematical concepts and skills necessary associated with teaching social studies at the elementary school stage.There is also a statistically significant difference (0.01) between the mean scores of the teachers in the results of the pre- and post-tests of mathematical concepts, and also in the results of the pre- and post-tests of the performance observation card. Finally, there is a positive correlation between the mastery of the mathematical concepts and skills needed to teach social studies among social studies teachers in the primary stage and their teaching performance.